Analisis Plasmodium Malaria dalam Sel Darah Merah (Eritrosit) melalui Segmentasi Warna dan Deteksi Tepi Sobel - Rinto Suppa; Astri Suppa Supratman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2019)
In this research, There were 9 images for training data and 26 images for test data. This image processing studied first carried out a cropping process on training data images. Then Pre-processing was also done to eliminated noise using the Salt and Pepper Noise method. After that, the RGB image results obtained were converted to grayscale images. Then the color segmentation process was based on the mean and standard deviation values. The edge detection process was then carried out using the sobel edge detection method and the results showed visible edge thickening on plasmodium. Through the color segmentation process, the percentage of plasmodium in the blood was <9%. In the process of identifying 26 test image data, 20 successful images and 6 images were declared failed to be identified. So the percentage of success of color segmentation in identification was 76.9% for 26 input data. Keywords : Sobel edge detection,color segmentation, plasmodium, image processing.